Ibn Qayyim al-Jawziyya and the divine attributes : rationalized traditionalistic theology - Ovadia, Miriam. (Islamic Philosophy, Theology and Science. Texts and Studies, 2018)
In Ibn Qayyim al-Jawziyya and the Divine Attributes Miriam Ovadia offers a thorough discussion on the hermeneutical methodology applied in the theology of the Ḥanbalite traditionalistic scholar Ibn Qayyim al-Jawziyya (d. 1350), the most prominent disciple of the renowned Ibn Taymiyya (d. 1328). Focusing on Ibn al-Qayyim's voluminous - yet so far understudied - work on anthropomorphism, al-Ṣawāʿiq al-Mursala , Ovadia explores his modus operandi in his attack on four fundamental rationalistic convictions, while demonstrating Ibn al-Qayyim's systemization of the Taymiyyan theological doctrine and theoretical discourse. Contextualizing al-Ṣawāʿiq with relevant writings of thinkers who preceded Ibn al-Qayyim, Ovadia unfolds his employment of Kalām ic terminology and argumentations; thus, his rationalized-traditionalistic authoring of a theological manifesto directed against his contemporary Ashʿarite elite of Mamluk Damascus.